Truth, control, and value motivations: the “what,” “how,” and “why” of approach and avoidance - Cornwell, James F. M.; Franks, Becca; Higgins, E. Tory (Frontiers in Systems Neuroscience, 2014)
The hedonic principle—the desire to approach pleasure and avoid pain—is frequently presumed to be the fundamental principle upon which motivation is built. In the past few decades, researchers have enriched our understanding of how approaching pleasure and avoiding pain differ from each other. However, more recent empirical and theoretical work delineating the principles of motivation in humans and non-human animals has shown that not only can approach/avoidance motivations themselves be further distinguished into promotion approach/avoidance and prevention approach/avoidance, but that approaching pleasure and avoiding pain requires the functioning of additional distinct motivations—the motivation to establish what is real (truth) and the motivation to manage what happens (control). Considering these additional motivations in the context of moral psychology and animal welfare science suggests that these less-examined motives may themselves be fundamental to a comprehensive understanding of motivation, with major implications for the study of the “what,” “how,” and “why” of human and non-human approach and avoidance behavior.